CHARACTERISTICS OF MODERN TECHNOLOGY IN THE DEVELOPMENT OF SPIRITUAL MATURITY OF STUDENTS OF HIGHER EDUCATION (American Journal of Pedagogical and Educational Research, 2024)
The article discusses the formation of a new type of student personality who can adequately act in a changing socio-cultural situation, that is, in higher education systems, the important factors are that the student is humane, able to change himself and society, and able to actively solve urgent problems of professional activity. This scientific article examines the current pedagogical activity in solving the above problems.